Compensatory responses can alter the form of the biodiversity–function relation curve. Issue 1901 (17th April 2019) - Thomsen, Matthias S.; Godbold, Jasmin A.; Garcia, Clement; Bolam, Stefan G.; Parker, Ruth; Solan, Martin
Abstract : There is now strong evidence that ecosystem properties are influenced by alterations in biodiversity. The consensus that has emerged from over two decades of research is that the form of the biodiversity–functioning relationship follows a saturating curve. However, the foundation from which these conclusions are drawn mostly stems from empirical investigations that have not accounted for post-extinction changes in community composition and structure, or how surviving species respond to new circumstances and modify their contribution to functioning. Here, we use marine sediment-dwelling invertebrate communities to experimentally assess whether post-extinction compensatory mechanisms (simulated by increasing species biomass) have the potential to alter biodiversity–ecosystem function relations. Consistent with recent numerical simulations, we find that the form of the biodiversity–function curve is dependent on whether or not compensatory responses are present, the cause and extent of extinction, and species density. When species losses are combined with the compensatory responses of surviving species, both community composition, dominance structure, and the pool and relative expression of functionally important traits change and affect species interactions and behaviour. These observations emphasize the importance of post-extinction community composition in determining the stability of ecosystem functioning following extinction. Our results caution against the use of the generalized biodiversity–function curve when generating probabilistic estimates of post-extinction ecosystem properties for practical application.